Fuchs endothelial corneal dystrophy: an updated review - Altamirano, Francisco; Ortiz-Morales, Gustavo; O’Connor-Cordova, Mario A.; Sancén-Herrera, Juan Pablo; Zavala, Judith; Valdez-Garcia, Jorge E. (International ophthalmology, 2024)
Purpose The present review will summarize FECD-associated genes and pathophysiology, diagnosis, current  therapeutic approaches, and future treatment perspectives. Methods Literature review. Results Fuchs' endothelial corneal dystrophy (FECD) is the most common bilateral corneal dystrophy and accounts for one-third of all corneal transplants performed in the US. FECD is caused by a combination of genetic and non-heritable factors, and there are two types: early-onset FECD, which affects individuals from an early age and is usually more severe, and late-onset FECD, which is more common and typically manifests around the age of 40. The hallmark findings of FECD include progressive loss of corneal endothelial cells and the formation of focal excrescences (guttae) on the Descemet membrane. These pathophysiological changes result in progressive endothelial dysfunction, leading to a decrease in visual acuity and blindness in later stages. The present review will summarize FECD-associated genes and pathophysiology, diagnosis, current therapeutic approaches, and future treatment perspectives. Conclusion With the characterization and understanding of FECD-related genes and ongoing research into regenerative therapies for corneal endothelium, we can hope to see more significant improvements in the future in the management and care of the disease.